INTERNALIZATION STRATEGY OF RABBANI CHARACTER VALUES FOR STUDENT PRIMARY SCHOOL (PIONIR: JURNAL PENDIDIKAN, 2023)
This article aims to examine strategies for internalizing rabbani character values in the learning process for high-class students at the favorite  Madrasah Ibtidaiyah in Lhokseumawe City. This study was born because character education in the millennial education system was developed only in learning/religious themes, even though it was written in the lesson plan that every lesson must contain aspects of character values. Ideally, Islamic education requires humans to have a rabbaniyyun character from an early age. This research is a qualitative research with data collection techniques using interviews, observation, and documentation. The results found in the form of rabbinic character values that were internalized by the teacher to high-class students at the favorite madrasah Ibtidaiyah in the city of Lhokseumawe were faith and obedience to Allah, distinguishing good and bad behavior, trustworthiness, forgiving each other, not taking drugs, not witnessing falsely, thinking and work hard, positive thinking, generous spirit, and help each other in goodness. While the strategies used by teachers to internalize the value of rabbinic character by strengthening the character of students from low grade, giving wise advice, reading and understanding the Qur'an, getting students to practice their knowledge, being grateful, being wise in speaking and attitude.Keywords: Strategy, teacher, internalization, rabbani character